aBRAZAdos project: a collaborative learning with conceptual maps. - Moura, Adelina (2008)
A project developed jointly by students from Carlos Amarante Secondary School (Braga, Portugal) and students from Santa Maria del Pilar School (Marianistas) (Saragossa, Spain). The primary goal of this project was that students from two different countries shared information about certain topics (history, population, city council, urban area, monuments holidays, etc.) relating to their towns. The students made conceptual maps about these topics and so they have checked that they have some characteristics which are common and others which are different. The name aBRAZAdos means Braga and Zaragoza hugged each other. The project has been developed on the Internet by students using IHMC CmapTools software, developed at the Institute for Human and Machine Cognition (IHMC). It enables users to construct, navigate, share, and make critical comments about knowledge models represented as Concept Maps. This software tool is free and can be downloaded from the IHMC web site together with the necessary technical support.